Utility of Activated Glassy Carbon and Pencil Graphite Electrodes for Voltammetric Determination of Nalbuphine Hydrochloride in Pharmaceutical and Biological Fluids. (27th January 2016) - Elqudaby, Hoda M.; Hendawy, Hassan A. M.; Souaya, Eglal R.; Mohamed, Gehad G.; Eldin, Ghada M. G.
Abstract : This work compares voltammetric response of nalbuphine hydrochloride (NP·HCl) at both activated glassy carbon and pencil graphite electrodes. The electrochemical oxidation of the drug was studied using cyclic voltammetry (CV), differential pulse voltammetry (DPV), and square wave voltammetry (SWV) techniques. For analytical purpose a well-resolved irreversible diffusion controlled voltammetric peak was established in Britton-Robinson (B-R) buffer solution of pH 6.00 using pencil graphite electrode (PGE). Using activated glassy carbon electrode (GCE) a well-resolved irreversible diffusion controlled voltammetric peak was obtained at pH 7.00 using the same buffer solution. According to the linear relationship between the peak current and NP·HCl concentration, DPV and SWV methods were developed for their quantitative determination in pharmaceutical and human biological fluids. The linear response was obtained in the range from1.6 × 10 - 5 to1.5 × 10 - 4  mol L −1 using PGE and from12.5 × 10 - 6 to13.75 × 10 - 5  mol L −1 using a GC electrode, respectively. Precision and accuracy of the developed method were checked by recovery studies.